SURVEY OF VO2 MAX ASPURA UNM FOOTBALL TEAM - Sudirman, Sudirman (UNIVERSITAS NEGERI MAKASSAR, 2020)
This study aims to determine the level of VO2 Max Aspura UNM football team. This research is descriptive with independent variable. The population of this study is the entire Players Football team Aspura UNM with the number of samples of 20 research people using saturated sampling technique. Data analysis technique used is descriptive analysis technique (percentage) by using system SPSS Version 16.00. Based on the results of data analysis, this study concludes that: from 20 samples of this study, mean = 35,37, median = 38,40, Range = 25,50, minimum value = 24,60, maximum value = 50,10, sum = 707.50. Based on Max VO2 recapitulation Aspura UNM football team It appears that from 20 samples of research that have excellent category as much as 2 people (9,1%), good category as many as 5 people (22,7%), medium category as many as 13 people (59,1% %), and bad category as much as 2 people (9,1%). Thus it can be concluded that the Max Level VO2 Team of the dominant UNM Team is in the medium category. Based on the purpose of this study, then as for the intended benefits are as follows: 1) The results of this study can be used as a source of information to sports actors about the level of VO2 Max. 2) As an information material for pest teachers, coaches and football coaches. 3) As a comparison material for students who are interested in conducting further research with due regard to the point of view of the wider proble.